2015
DOI: 10.1111/jvim.13617
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Brain Tumor Treatment in Dogs

Abstract: Intracranial neoplasia is commonly diagnosed in dogs and can be treated by a variety of methods, but formal comparisons of treatment efficacy are currently unavailable. This review was undertaken to summarize the current state of knowledge regarding outcome after the treatment of intracranial masses in dogs, with the aim of defining optimal recommendations for owners. This review summarizes data from 794 cases in 22 previously published reports and follows PRISMA guidelines for systematic review. A Pubmed sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
127
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 40 publications
3
127
0
4
Order By: Relevance
“…A few studies have reported SUDEP in veterinary medicine [33, 34], but its mechanisms remain unknown. In humans, patients at highest risk for SUDEP show occurrence of generalized tonic-clonic seizures, poor seizure control, a young age, and multiple AED treatment [35]. Here, the two dogs with suspected SUDEP died at a relatively young age (6.1 and 7.3 years) and had a very high epileptic seizure frequency (≥1 sz/week) with a poor response to at least one AED treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have reported SUDEP in veterinary medicine [33, 34], but its mechanisms remain unknown. In humans, patients at highest risk for SUDEP show occurrence of generalized tonic-clonic seizures, poor seizure control, a young age, and multiple AED treatment [35]. Here, the two dogs with suspected SUDEP died at a relatively young age (6.1 and 7.3 years) and had a very high epileptic seizure frequency (≥1 sz/week) with a poor response to at least one AED treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, median survival time in neoplastic and inflammatory disease was 13.7 and 54.1 months, respectively. Previously, median survival time in dogs with neoplastic disease that received symptomatic treatment, and inflammatory disease that received immunosuppressive treatment, were reported as approximately 2.2–23.3 months [35] and 77.5 months [36], respectively. Therefore, it is important for survival of dogs with StE to recognize sub-classification by signalment, clinical course, and MRI/CSF findings.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similar to human patients, the prognosis for dogs with brain tumors is poor with a median survival of 65 days (4 studies, 138 dogs) with symptomatic therapy only, 312 days (6 studies, 108 dogs) with surgical treatment, and 351 (13 studies, 428 dogs) with radiation therapy. 20 Occasionally, long-term survivors live 2.5 to 5 years with multimodal therapy; although dogs with intra-axial tumors, which are predominantly gliomas, were not typically in this long-lived group. 20,21 …”
Section: Brain Tumor Surrogatesmentioning
confidence: 99%
“…20 Occasionally, long-term survivors live 2.5 to 5 years with multimodal therapy; although dogs with intra-axial tumors, which are predominantly gliomas, were not typically in this long-lived group. 20,21 …”
Section: Brain Tumor Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation